2004
DOI: 10.1194/jlr.m400233-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing the expression of cholesterol transporters (StAR, MLN64, and SCP-2) on bile acid synthesis

Abstract: There are two major pathways of bile acid synthesis: the "neutral" pathway, initiated by highly regulated microsomal cholesterol 7 ␣ -hydroxylase (CYP7A1), and an "alternative" pathway, initiated by mitochondrial sterol 27-hydroxylase (CYP27A1). In hepatocyte cultures, overexpression of CYP7A1 increases bile acid synthesis by Ͼ 8-fold. However, overexpression of CYP27A1 in hepatocytes only increases it by 1.5-fold, suggesting that additional rate-limiting steps must be involved in the regulation of this pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 26 publications
3
60
1
Order By: Relevance
“…The cells were sedimented by centrifugation and the pellets were washed three times by resuspension and sedimentation. Subcellular fractions, microsomal, cytosol, and nuclear, were isolated as previously described (19). The cellular or subcellular pellets were resuspended in 0.3 ml of PBS.…”
Section: Determination Of Cholesterol Biosynthesis By Tlc and Hplcmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were sedimented by centrifugation and the pellets were washed three times by resuspension and sedimentation. Subcellular fractions, microsomal, cytosol, and nuclear, were isolated as previously described (19). The cellular or subcellular pellets were resuspended in 0.3 ml of PBS.…”
Section: Determination Of Cholesterol Biosynthesis By Tlc and Hplcmentioning
confidence: 99%
“…Microsomal fractions were isolated as previously described (19). Microsomal or total extracted proteins from the treated cells were separated on a 7.5% SDS-polyacrylamide denaturing gel.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the liver, MLN64 could mobilize cholesterol into mitochondria where it should be oxidized in the first step of the acidic pathway for bile acid synthesis [17] . Indeed, Pandak et al [18] and Ren et al [19,20] demonstrated that overexpression of the closest homologue of MLN64 in liver cells, StAR, leads to an important increase in bile acid synthesis both in vitro and in vivo. However, MLN64 overexpression in primary rat hepatocytes produced only a 20% increase in the rate of bile acid synthesis, suggesting that the hepatic expression of this protein is not a major determinant of the transport of cholesterol to the mitochondria during bile acid synthesis [19] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the first reported roles for STARD1 outside of steroidogenic cells was in cholesterol transfer across the mitochondrial membranes in the liver for initiation of bile acid synthesis by the alternative pathway. Overexpression of STARD1 significantly increases 27HC and bile acid synthesis in primary rat or mouse hepatocytes or human HepG2 hepatoma cells (Pandak et al 2002, Ren et al 2004a,b, Hall et al 2005. Enhanced rates of bile acid synthesis also occur in both rats and mice after overexpression of STARD1 in the liver, providing evidence for an in vivo function (Ren et al 2004a,b).…”
Section: Stard1 and Oxysterol Production In Non-steroidogenic Tissuesmentioning
confidence: 99%